[Alfréd Ruby 14]
Siófok big camp-fire, to Héviz with trabant sun-set, Sárvár open-air bath, Jánosháza, Tapolca swans, Zalaszánto old church, photos about Ferenc Deák & others, Bulgaria Gold Coast, the wiew from the hotel, botanical garden, Sunny-coast photo on camel, seagalls, to Szentes with trabant, procession, Kisoroszi, flood on the Danube, Budapest Tram & cars on the Elisabeth-bridge, at home